Energy Trading in P2P Network by using Blockchain in Smart Grid - Ahmed, Afshaar; Yasir Ali, Agha; Ahmed, Mishaal; Lateef Khan, Abdul; Ahmed, Manzar; Amin, Uzma (2022)
In recent years, the dramatic increase in demand of electricity utilization has introduced various environmental and sustainability concerns for Conventional Energy Grid based on fossil fuels, which driving the global energy manufacturers to adapt new efficient and resilient energy systems. The conventaional Grid is based on centralized system suffer from power losss, theft cases and cannot adopt new power systems properly. Presently the focus of the scientist and researchers is on the Clean Energy resources and Smart Grid, which has potential to address the contemporary problems found in conventional energy system. On the other side , Smart is a new technology, which allows the integration of clean energy resources such as wind, solar, geothermal, hydro, biomass, and tidal energy systems, ensuring energy availability at all times. The quintessential purpose of renewable technologies is to contrive a sustained community. Nevertheless, it has become a challenging concern for Smart Grid to integrate and coordinate enormous consignment of expanding users and connections. Consequently, blockchain has emerged as a resilient technology in various industries offering data integrity, security, building trust between parties, data immutability, and secure communication. These feature of blockchain making it an auspicious technology for decentralized Smart Grid and Renewable Energy criterion. In this research work, a blockchain based energy trading modal using Peer-to-Peer transactions management is presented. The main goal is to investigate an energy-trading model based on crypto wallets as a digital currency using smart grid and renewable energies. Moreover, contemporary issues of industrial and commercial communities adopting renewable Energy system will be address.